Choosing the precision of performance metrics - CRANE, Alan D. (Institutional Knowledge at Singapore Management University, 2018)
There is a standard trade-off in contracts between the provision of incentives and insurance. We hypothesize that this trade-off influences the precision with which firm performance is measured. We find that firm outcomes are measured less precisely when chance plays a large role in these outcomes. Further, this precision is determined through the choice of shares outstanding. This has several novel implications. Nominal stock prices can remain constant over time, and firms with unpredictable cash flows should have more shares and lower stock price levels, all else equal. We find evidence consistent with these implications.